Students' Perception on the Use of WhatsApp in Learning EFL during Covid 19 at Remote Area - Nur Lindawati; Baso Jabu; Sultan Baa (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The aim of this study was to find out the students' perception on the use of WhatsApp in learning EFL During covid 19 at remote area (Study at SMPN 11 Selayar Island South Sulawesi). The researchers applied mixed method (quantitative and qualitative) research design. The data of this research were collected through questionnaire and interview. The subjects of this study were students of SMPN 11 Selayar. The sample of the questionnaire was 50 students and Interviews of eight students were taken using purposive sampling technique. The results of data analysis showed that (1) positive student perceptions on the use of WhatsApp in learning EFL during Covid-19 at remote area with the classification, 7(14%) students classified Strongly positive, 38 (76%) students classified Positive, 4(8%) students were classified as Medium, 1 (2%) student were classified as Negative and not there are students who were classified as strongly negative. (2) Student explanations in interviews regarding the perception on the use of WhatsApp in learning EFL during Covid-19 at remote area explained that WhatsApp is a good online learning tool because WhatsApp has good features that really support EFL learning in this pandemic era. Even though there is a pandemic, students can still learn EFL through WhatsApp because in WhatsApp students and teachers can still interact and discuss well.